A REVIEW OF BIOPHILIC FACTOR FOR HOTEL DESIGN IMPLEMENTATION IN BATAM - Victor Agustian; Jeanny Laurens Pinassang (Journal of Architectural Research and Education, 2022)
Batam City has a high potential in the tourism sector and attract tourists for natural tours, shopping tours, culinary tours, sports tours ,etc. In addition, Batam City is a destination for local people outside Batam to find work, because of many manufacturers (local or foreign companies) have established in Batam. The developments triggered a significant increase in population. As the effect of population growth, development in Batam city is also growing. It has a major impact on the reduction of green space. Many buildings have been created only focusing on their strategic location and the beauty of their exterior design. Therefore, the next development in Batam city must be controlled, so that there is a balance with the environment and doesn’t cause the new problem in the future.In other side, young people nowadays, who are in productive age, demand comfort and practical life. Staying in a hotel (for work or vacation) is a new desire for them to adapt to their modern lifestyle. To meet the demands of modern life and to overcome the potential problems that will arise in the future, the need to realize an environmentally friendly hotel is a must. Biophilic is a concept strategy modified by the addition of green plants as a guide to balancing biotic life in the environment. Biophilic design has embodied an auspicious momentum in human’s relationship with nature. The Implementation of a biophilic hotel design is awaited and will encourage the environment by using the same concept in the future